INTERPRETATION POSSIBILITIES OF DISC TYPE SOURCES ELECTRIC FIELDS - Hloba, Y.; Hloba, R.; Reva, M.; Vyzhva, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
As a result of aging of the protective insulation layer of underground pipelines, which occurs under the influence of external factors, in the insulating protective layer can form places where the insulation is damaged that cause a leakage of electric current under the protective potential of the pipe. These processes lead to a decrease in the protective potential of underground pipelines, and thus to a deterioration in the protection of underground utility system. Such damage locations are recorded by surveying the distribution of the electric potential "soil-pipe" (Usp) along the pipeline route by the remote electrode and measuring the "transverse and longitudinal gradients" of the electric field. Since the places of electric current leakage are sources of electric fields, it is important to know the features of these fields in order to assess the degree and extent of damage. From a fundamental point of view, this question comes down to solving the inverse problem of electrometry for fields created by different structure sources. In the case of detailing anomalies, it is desirable to obtain electrometric survey data with an accuracy that allows to apply for their quantitative interpretation methods that base on analytical relationships for anomalies of these parameters. In this paper there is an analysis of the possibilities of using methods which is appropriate for fields created by point sources to interpret the anomalous field caused by a source of leakage current of the disk type damage.